Redesigning business model options for university of the future through humanizing education and IR4.0 - Mahyuddin, Azratulham; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
The specked compression placed on the university have created discussion about the need to find new the role of universities to serve the community in the better way. In reality, local universities face some difficulties with fees and graduation which make the universities’ value less attractive. Business modeling tools such as Business Model Canvas (BMC), Value Proposition Design (VPD), and Environmental Maps (EM) should be applied and used in the strategy canvas for universities in order to survive in the new era and to ideate the best design strategy for the University of the Future (UoF). In the other hand, the new existence of digital transformation supports the universities to become the best marketing tools in their business. Without failed to mention, humanizing education also should be implemented within the universities in order to keep the balance of human and technology and to stay relevant for the future. This paper provides the strategies and plans to transform the university into a radiant institution with its own personality.